Endoscopic papillary balloon dilation for a 7‐year‐old girl with choledocholithiasis. Issue 2 (16th April 2013) - Sogo, Tsuyoshi; Kondo, Takeo; Tsunoda, Tomoyuki; Murayama, Akitoshi; Komatsu, Haruki; Inui, Ayano; Fujisawa, Tomoo
Abstract A 7‐year‐old girl was referred to our hospital for severe abdominal pain and elevated serum levels of amylase and aminotransferase. Radiological examinations revealed choledocholithiasis. EPBD was performed under intravenous anesthesia using midazolam and ketamine chloride. After fluoroscopic confirmation of a bile duct stone, a dilation balloon (30 mm‐long, 8 mm‐diameter) was passed over the guidewire and placed across the papilla. The balloon was gradually inflated until the notch created by the papillary sphincter disappeared. At 4 atm, the notch disappeared and the pressure was maintained for 15 s. Stone extraction was performed by using a retrieval balloon catheter. Abdominal pain disappeared immediately after EPBD, and she resumed oral intake 2 days after EPBD. In conclusion, EPBD may be a safe and effective technique for the treatment of choledocholithiasis in pediatric patients. EPDB should be selected as a treatment for pediatric choledocholithiasis in view of its advantages of preserving papillary function.